Reversal: The Colonial Afterlife and Nostalgia - Timoteus Anggawan Kusno (Retorik: Jurnal Ilmu Humaniora, 2025)
This experimental essay unfolds as a journey through memory, ruins, and rituals, tracing the lingering presence of a colonial past in contemporary Indonesia. It explores the layered relationship between colonialism, postcolonial nation-building, and the enduring structures of imperial power that continue to shape cultural and political life. At its centre is a paradox: in pursuing national unity, the newly independent state often reproduced the very systems of control it aimed to dismantle. Colonial nostalgia, expressed through aesthetic revivals, architectural restoration, and performative rituals, emerges not only as a sentiment but as a structural force within collective memory. Through a weaving of critical reflection and poetic interludes, the essay invites readers to reflect on the shifting boundary between history and feeling. It lingers in what is remembered but also in what is imagined, suppressed, and restaged.